2005
DOI: 10.1111/j.1460-9568.2005.04528.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of photoperiodic history on clock genes and the circadian pacemaker in the rat retina

Abstract: The influence of seasonal lighting conditions on expression of clock genes and the circadian pacemaker was investigated in the rat retina. For this purpose, the 24-h profiles of nine clock genes (bmal1, clock, per1, per2, per3, dec1, dec2, cry1 and cry 2) and the arylalkylamine N-acetyltransferase gene as an indicator of the circadian pacemaker output were compared between light-dark periods of 8 : 16 and 16 : 8 h. The photoperiod influenced the daily patterns of the amount of transcript for per1, per3, dec2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…The results obtained indicated that the circadian regulation of aanat mRNA is affected by the photoperiodic history (33, 34) thus suggesting that the pacemaker driving aanat transcription in the photoreceptors can store photoperiodic information in a manner similar to that reported for SCN. Another similarity between the SCN clock and the pacemaker driving aanat transcription in the retina has been reported with the respect to the effect of restricted feeding in the rat retina (35).…”
Section: Regulation Of Retinal Melatonin Synthesis By Circadian Clocksmentioning
confidence: 64%
“…The results obtained indicated that the circadian regulation of aanat mRNA is affected by the photoperiodic history (33, 34) thus suggesting that the pacemaker driving aanat transcription in the photoreceptors can store photoperiodic information in a manner similar to that reported for SCN. Another similarity between the SCN clock and the pacemaker driving aanat transcription in the retina has been reported with the respect to the effect of restricted feeding in the rat retina (35).…”
Section: Regulation Of Retinal Melatonin Synthesis By Circadian Clocksmentioning
confidence: 64%
“…BHLHB3 is a clock gene (19, 20), a transcriptional repressor (18) and importantly a tumor suppressor in lung cancer (21). In D-HEp3 cells BHLHB3 is induced by p38 and was positively linked to genes involved in extracellular matrix biology (e.g., collagen-I α1, MMP2) (Fig1B).…”
Section: Resultsmentioning
confidence: 99%
“…The clock of photoreceptors resembles the central clock in the SCN in being autonomous, capable of storing photoperiodic information (Rohleder et al. 2006), and insensitive to feeding patterns (Oishi et al.…”
Section: Discussionmentioning
confidence: 99%